Ghrelin Protects Lipopolysaccharide-Induced Acute Lung Injury Rats against Pulmonary Vascular Dysfunction by Inhibiting Inflammation - Guang Li; Chen-Liang Zhou; Wen-Fang Xia; Di Zhang; Hui-Qing Lin (Canadian Respiratory Journal)
Objective. To determine the effect and mechanism of the anti-inflammatory agent ghrelin on pulmonary vascular dysfunction (PVD) in lipopolysaccharide- (LPS-) induced acute lung injury (ALI) rat models. Methods. Thirty-two adult male Sprague Dawley rats (n = 16/group) were randomly divided into ghrelin and saline groups, wherein ghrelin (10 nmol/kg) or saline was subcutaneously administered. After 30 min, eight rats from each group were randomly selected, and LPS (5 mg/kg) or saline was administered by intratracheal instillation to induce ALI. Four hours after establishing the ALI rat model, the mean pulmonary arterial pressure (mPAP), mean right ventricular systolic pressure (RVSP), levels of proinflammatory cytokines tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in the bronchoalveolar lavage fluid (BALF), BALF cell count, wet-to-dry (W/D) lung weight ratios, and myeloperoxidase (MPO) activity in lung tissue for all four groups (ghrelin, ghrelin + ALI, saline, and saline + ALI) were measured. Immunohistochemical staining to detect alpha-smooth muscle actin (α-SMA) and proliferating cell nuclear antigen (PCNA) expression was performed to assess the intrapulmonary arterial wall thickness and the proliferation of smooth muscle cells, respectively. Results. The ghrelin-pretreated ALI rats showed lower mPAP, RVSP, PCNA expression, MPO activity, W/D lung weight ratio, TNF-α and IL-6 levels, and BALF cell count than the saline-pretreated ALI rats, but ghrelin had no effect on the intrapulmonary arterial wall thickness of ALI rats. Conclusion. Our results confirmed the association between inflammation and PVD in ALI and suggested that the suppression of inflammation by ghrelin pretreatment could protect LPS-induced ALI rats against PVD.